Validity of the Japanese version of the Munich ChronoType Questionnaire. (August 2014) - Kitamura, Shingo; Hida, Akiko; Aritake, Sayaka; Higuchi, Shigekazu; Enomoto, Minori; Kato, Mie; Vetter, Céline; Roenneberg, Till; Mishima, Kazuo
<x xml:space="preserve">Abstract</x> To assess circadian preference with a score, the Morningness-Eveningness Questionnaire (MEQ) has been used for more than 3 decades now. More recently, the Munich ChronoType Questionnaire (MCTQ) was developed: it asks for sleep-wake behavior on work and free days and uses the midpoint of sleep on free days (MSF), corrected for sleep debt accumulated during the work week as an indicator of chronotype (MSFsc). In this study, we developed a Japanese version of the MCTQ by using a translation/back-translation approach including an examination of its semantic validity. In a subsequent questionnaire survey, 450 adult men and women completed the Japanese versions of the MCTQ and MEQ. Results showed that MEQ scores were significantly negatively correlated with mid-sleep parameters assessed by the MCTQ, on both, work and free days, as well as with the chronotype measure MSFsc (r = −0.580 to −0.652, all p < 0.001). As in the original German version, the strongest correlation was observed between MEQ score and MSF. A physiological validation study using dim light melatonin onset as a circadian phase marker (N = 37) showed a high correlation between chronotype as assessed with the MSFsc (r = 0.542, p < 0.001), and less so for MEQ score (r = −0.402, p = 0.055). These results demonstrate the validity of the Japanese MCTQ and provide further support of the adequacy of the MCTQ as a chronotype measure.